Research into the effect of ammunition belt stiffness on the operation of automatic firing systems using experimental methods - Vo, Bien V.; Nguyen, Phon D.; Nguyen, Phu M.; Vu, Long X. (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: This article focuses on determining the dynamic characteristics of the automatic firing system through experimental methods. Additionally, the study mentions the impact of ammunition belt stiffness. Methods: The research findings include the displacements of the basic part (bolt carrier) and the ammunition belt of automatic weapons during firing series. To measure and determine these parameters, a high-speed camera model FASTCAM SA1.1, specifically the 675K-C1 variant, was utilized. The elastic force between the belt links was determined using deformation stamps equipped with force-measuring sensors. To validate the reliability of the method, experiments were conducted on the PKMS machine gun. Results: The results obtained show that, when using a tape with a stiffness of 42 [N/mm], the kinematic characteristics of the basic link such as recoil velocity and recoil time change significantly compared to using a tape which has a stiffness of 98 [N/mm]. In particular, the maximum recoil velocity of the base gun can be reduced by 8% when firing a series of 6 bullets. These results can be applied in calculations and designs to optimize the structure of the ammunition belt and the automatic firing system. Furthermore, these findings can aid in calculating the firing rate of the gun, thus facilitating the operation of automatic weapons. Conclusion: The testing procedure developed in this study serves as a crucial theoretical foundation for evaluating and determining the dynamic characteristics of other automatic weapon systems.